ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - Akip, M; Mastiah, Mastiah; Siti, Siti (STKIP Melawi, 2024)
Abstact : The purpose of this study is to describe the values of character education in the novel Guru Aini by Andrea Hirata. This type of research is library research or Library Research. The approach used is a qualitative approach. 16 values of national character education contained in the novel